Paradoxes of Ratification: The Nagoya Protocol and Brazilian State Transformations. (March 2022) - Eimer, Thomas R.; Donadelli, Flavia
This article explores the paradoxical behaviour of Brazil in relation to its national and international approaches to the regulations of access to genetic resources and benefits sharing with indigenous and other traditional communities. Brazil was one of the leaders in the international negotiations that led to the UN Nagoya Protocol but only ratified it 11 years later, after remarkable transformations of its internal biodiversity laws. We suggest that the seemingly contradictory behaviour has been shaped by the country's internal political and ideological changes. This transformation goes hand in hand with substantial changes in state–society relations, particularly with regard to the balance of coalitions' power between indigenous groups and industrial and agrarian elites. The article builds on the literature on state transformations and relies on the Advocacy Coalition Framework to show the importance of considering the impact of national-level politics on the fate of international agreements.